Cryoballoon versus radiofrequency guided by ablation index for atrial fibrillation ablation: a retrospective propensity-matched study. (14th October 2021) - Ribeiro Queiros, P; Fonseca, P; Almeida, J; Silva, G; Silva, M; Teixeira, R; Oliveira, M; Goncalves, H; Dias Ferreira, N; Primo, J; Fontes-Carvalho, R
Abstract: Background/Introduction: Radiofrequency (RF) and cryoballoon (CB) ablation are established techniques for the treatment of atrial fibrillation (AF). Randomized trials comparing both techniques show similar levels of success; however, studies comparing CB with RF guided by ablation index (AI) are lacking. Purpose: To compare the treatment success of CB with RF guided by AI, in patients with paroxysmal or persistent AF undergoing their first ablation procedure. Methods: Patients undergoing AF ablation between 2017 and 2019 were retrospectively analysed. Primary success outcome was freedom from recurrence (defined as any episode of AF, atrial flutter or atrial tachycardia lasting >30 seconds and occurring after 91 days from ablation, or need for antiarrhythmic drugs (AAD), cardioversion or redo procedure). Secondary end-point was a composite of adverse cardiovascular outcomes (stroke/TIA, emergency room visit for AF, hospitalization for AF or cardiovascular death). Analysis was done before and after propensity score matching. Results: A total of 316 patients were included. Mean age was 56.9±11.7 years. Sixty-two percent were male (n=196). Paroxysmal AF was present in 80.7% (n=255), with no difference between groups. RF was used in 57.9% (n=183) and CB in 42.1% (n=133), with isolation of all pulmonary veins accomplished in 95.9% (n=302), without differences between groups. Mean CHA2DS2-VASc score was 1.5±1.3, being higher in the RF group (1.7±1.3 vs 1.2±1.1; p=0.03); these patients were also older (mean age 58.1±12.0 vs. 55.17±11.0 years; p=0.007) and more likely to be in AF at the ablation (26.7% vs. 16.5%; p=0.006), have chronic kidney disease (40.2% vs. 23.2%; p=0.002), anaemia (11.8% vs. 2.7%; p<0.001), moderate/severe mitral disease (17.5% vs. 7.4%; p=0.012) or history of atrial flutter (17.7% vs. 3.1%; p<0.001). Patients in the CB group had a longer history of AF (3.8±3.5 vs. 3.0±2.9 years; p=0.041), received treatment with AAD more often (60.9% vs. 55.9%; p=0.049) and had longer follow-up time (889±397 vs. 601±239 days; p<0.001). Mean freedom from recurrence was not significantly different between groups (1106 days for CB vs. 889 days for RF; p=0.793), and recurrence rates were also similar (27.8% for CB vs. 23.5% for RF; p=0.291); however, patients treated with CB were more likely to need a redo procedure (38.3% vs. 17.4%; p=0.025). There were no differences in the composite of adverse cardiovascular events or in individual outcomes. Propensity score matching was done, and 154 patients were matched 1:1 for each treatment group. Survival free from recurrence showed no differences (1060 days for CB vs. 864 days for RF; p=0.912), and neither did the recurrence rate. CB patients with recurrence were still more likely to need a redo procedure (37.9% vs. 11.1%; p=0.021). Conclusion: RF and CB result in similar survival free from AF and AF recurrence; however, recurrence in CB seems more significant, leading to higher rates of redo procedures. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Centro Hospitalar de Vila Nova de Gaia/Espinho